The Efficacy of Platelet-Rich Plasma in the Treatment of Rib Fractures - Gunay, Samil; Candan, Huseyin; Yılmaz, Rahsan; Eser, Irfan; Aydoğmus, Umit (The Thoracic and Cardiovascular Surgeon, 2017)
Background Rib fracture is the most common result of thoracic traumas. Intrapulmonary shunt, alveolar capillary membrane damage, intra-alveolar hemorrhage, and hypoxia may develop following rib fractures. Therefore, prompt treatment is important. The aim of this experimental study was to analyze the effects of platelet-rich plasma (PRP) on rib fractures to secure a speedier and more efficient treatment method.Materials and Methods The study involved 18 New Zealand white rabbits, randomly divided into three groups as Group 1, the sham group with no surgical intervention; Group 2, the control group in which simple rib fractures were applied and no treatment; and Group 3, in which rib fractures were applied and then PRP treatment was administered.Results The mean recovery plate thickness measurements were found to be statistically significantly higher in the PRP group compared with the other groups (p < 0.005). A thicker fibrotic cell proliferation and the formation of many capillaries were observed around the growth plate in the PRP group compared with the other groups. These structures were lesser in the control group compared with the PRP group and at the lowest level in the sham group. Larger and distinct callus formation was observed and a new intramedullary field in the PRP group.Conclusions PRP is a reliable and effective autologous product with minimal side effects, which can be considered as an alternative treatment in patients with rib fractures and used easily in pseudoarthrosis, surgical fracture, or flail chest.
Keywords: platelet-rich plasma; rib fractures; trauma